THE EFFECT OF LEADERSHIP, WORK MOTIVATION AND RECRUITMENT ON EMPLOYEE PERFORMANCE AT PT. TUNAS AUTO GRAHA - Rahman, RZ M (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2024)
The purpose of this study was to determine the effect of leadership, work motivation and recruitment on employee performance at PT Tunas Auto Graha. The sample size taken was 100 employees at PT Tunas Auto Graha. The sampling technique was purposive sampling, where the respondents taken were some of the employees at PT Tunas Auto Graha. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 32 statement items. The analysis technique used is multiple linear regression analysis. The results showed that Leadership, Work Motivation and Recruitment simultaneously had a significant effect on employee performance.